A REVIEW OF DAMAGE CASE HISTORIES AND METHODS FOR THE PROTECTION OF UNDERGROUND STRUCTURES IN CASE OF EARTHQUAKE AND BLAST LOADS (Malaysian Journal of Civil Engineering, 2018)
Underground facilities are an integral part of the infrastructure of modern society and are used for a wide range of applications, including subways and railways, highways, material storage, and sewage and water transport. Underground facilities built in areas subject to earthquake activity must withstand both seismic and static loading. Historically, underground facilities have experienced a lower rate of damage than surface structures. Nevertheless, some underground structures have experienced significant damage in recent large earthquakes, including the 1995 Kobe, Japan earthquake, the 1999 Chi-Chi, Taiwan earthquake and the 1999 Kocaeli, Turkey earthquake. In order to understand the behavior of underground structure during earthquake and blast loads, a wide collection of case histories has been reviewed from the available literature and some of them have been described in detail. Criteria are also shown in the papers which are used to classify the damage database. Such a classification involves entity and type of damage and is aimed to highlight the possible causes of damage, in order to improve performance- based seismic design of tunnels. This article presents a summary of the current state of seismic analysis and design for underground structures.